Abdominal wall complications after kidney transplantation: A clinical review. Issue 12 (28th October 2021) - Gioco, Rossella; Sanfilippo, Claudio; Veroux, Pierfrancesco; Corona, Daniela; Privitera, Francesca; Brolese, Alberto; Ciarleglio, Francesco; Volpicelli, Alessio; Veroux, Massimiliano
Abstract: Introduction: Abdominal wall complications are common after kidney transplantation, and although they have a minor impact on patient and graft survival, they increase the patient's morbidity and may have an impact on quality of life. Abdominal wall complications have an overall incidence of 7.7–21%. Methods: This review will explore the natural history of abdominal wall complications in the kidney transplant setting, with a special focus on wound dehiscence and incisional herni, with a particular emphasis on risk factors, clinical characteristics, and treatment. Results: Many patient‐related risk factors have been suggested, including older age, obesity, and smoking, but kidney transplant recipients have an additional risk related to the use of immunosuppression. Wound dehiscence usually does not require surgical intervention. However, for deep dehiscence involving the fascial layer with concomitant infection, surgical treatment and/or negative pressure wound therapy may be required. Conclusions: Incisional hernia (IH) may affect 1.1–18% of kidney transplant recipients. Most patients require surgical treatment, either open or laparoscopic. Mesh repair is considered the gold standard for the treatment of IH, since it is associated with a low rate of postoperative complications and an acceptable rate of recurrence. Biologic mesh could be an attractive alternative in patients with graft exposition or infection.